2022
DOI: 10.2147/ijgm.s337455
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Value of Enhanced CT Radiomics Analysis in the Differential Diagnosis Between Pancreatic Cancer and Chronic Pancreatitis

et al.

Abstract: To investigate the feasibility of enhanced computed tomography (CT) radiomics analysis to differentiate between pancreatic cancer (PC) and chronic pancreatitis. Methods and materials:The CT images of 151 PCs and 24 chronic pancreatitis were retrospectively analyzed in the three-dimensional regions of interest on arterial phase (AP) and venous phase (VP) and segmented by MITK software. A multivariable logistic regression model was established based on the selected radiomics features. The radiomics score was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Although EUS has enhanced the diagnosis of pancreatic lesions to some extent, it is extremely dependent on the endosonographer's Currently, the feasibility of machine learning radiomics in diagnosing PDAC has been demonstrated using CT, MRI, PET-CT, and US images. [29][30][31][32][33][34][35] an AUC of 0.96. 34 Although growing numbers of studies have shown that machine learning-based radiomics models achieve good performance in identifying PDAC and benign pancreatic lesions, some common limitations remain unresolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EUS has enhanced the diagnosis of pancreatic lesions to some extent, it is extremely dependent on the endosonographer's Currently, the feasibility of machine learning radiomics in diagnosing PDAC has been demonstrated using CT, MRI, PET-CT, and US images. [29][30][31][32][33][34][35] an AUC of 0.96. 34 Although growing numbers of studies have shown that machine learning-based radiomics models achieve good performance in identifying PDAC and benign pancreatic lesions, some common limitations remain unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the feasibility of machine learning radiomics in diagnosing PDAC has been demonstrated using CT, MRI, PET‐CT, and US images 29–35 . Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…By leveraging high-dimensional feature spaces, radiomics enables the discovery of complex patterns and correlations that may not be readily apparent through traditional visual inspection by physicians (or radiologists). Consequently, radiomics has shown promise [6–8,44] in improving diagnostic accuracy with an AUC of 0.7–0.8, depending on the specific dataset and implementation [9 ▪ ,10 ▪ –12 ▪ ,13 ▪▪ ,14 ▪ ].…”
Section: Radiomicsmentioning
confidence: 99%
“…A common practice in these studies is to use feature selection methods to identify the most relevant radiomics features for tumor classification. Ma et al [9 ▪ ] and Flammia et al [13 ▪▪ ] both utilized the least absolute shrinkage and selection operator (LASSO) method to select features that were then integrated into their respective models. LASSO is a linear regression analysis method often used in statistics and machine learning as a regularization strategy to prevent overfitting.…”
Section: Radiomicsmentioning
confidence: 99%
“…With the rapid development of medical imaging technologies, radiomics has begun to be used in the differential diagnosis of MFCP and PDAC (21)(22)(23)(24)(25)(26)(27). For example, Deng et al (24) studied 96 patients with PDAC and 23 patients with MFCP.…”
Section: Differentiating Mass-forming Chronic Pancreatitis From Pancr...mentioning
confidence: 99%